Plan de Negocios para el montaje y constituciòn de una empresa procesadora de cerveza artesanal en la ciudad de Cartagena - Ramos Ortiz, Valeria Alexandra; Sierra Palomino, Diraina Andrea (Universidad Antonio Nariño, 2023)
This research project seeks to establish the level of approval of craft beer among the clientele of similar drinks in the city of Cartagena. In this business prospectus, the possibility of the consumption of craft beer by the population is added, establishing the nature, dimension and hierarchy of the needs and fundamental problems that stand out in the sector that is the subject of this study, taking as a specific target market the people of medium-high socioeconomic level, aged between 20 and 65 years respectively, and having as a marketing market the beverage outlets in the city of Cartagena such as nightclubs and bars, the differential value of this project is mainly to highlight the Colombian traditions in a different way, both for citizens and foreigners, by adapting local foods in varieties of high quality craft beer, in this way, "Harlequín" will contribute to the economic and social development of local farmers and producers by buying and distributing their products. The methodology by which the research will be carried out will be descriptive, the primary research tools will be made up of direct observation and the application of surveys, while the secondary information tools will be made up of documents, newspapers and magazines, page reports the internet and various social networks. In the economic and financial study it was established that the initial investment of the determined project is $38,517,687, and a high financial potential is obtained starting from positive consolidated at the NPV level with 73,093,881, a PRI of 1.13 and finally an IRR of 45.73% was obtained, which shows that the investment project is feasible and profitable.